The bond premium in a DSGE model with long-run real and nominal risks - Glenn D. Rudebusch; Eric T. Swanson (National Bank of Belgium, 2008)
The term premium on nominal long-term bonds in the standard dynamic stochastic general equilibrium (DSGE) model used in macroeconomics is far too small and stable relative to empirical measures obtained from the data - an example of the "bond premium puzzle." However, in models of endowment economies, researchers have been able to generate reasonable term premiums by assuming that investors face long-run economic risks and have recursive Epstein-Zin preferences. We show that introducing these two elements into a canonical DSGE model can also produce a large and variable term premium without compromising the model's ability to fit key macroeconomic variables.
Keywords: 330; Anleihe; Intertemporale Entscheidung; Zinsstruktur; Indexbindung; Dynamisches Gleichgewicht; Theorie; USA